DEPLOYMENT OF TECHNOLOGIES IN CURTAINING EXAMINATION MALPRACTICES IN NIGERIA TERTIARY EDUCATION - Galadima, Farida Ibrahim; JAE, Talatu (Multi-Disciplinary Research and Development Journals Int’l, 2025)
Examination malpractice remains a serious threat to academic integrity in Nigeria’s tertiary institutions, undermining the credibility of degrees, diminishing public trust, and devaluing genuine student achievement. As cheating becomes more sophisticated—with the involvement of smartphones, hidden devices, social media, and impersonation—traditional monitoring and punishment methods are increasingly inadequate. This chapter investigates how technology is being deployed to counter examination malpractice in universities, polytechnics and colleges of education. Specifically, it reviews technological tools such as biometric verification, computer-based testing, CCTV surveillance, secure digital question management, online proctoring, AI-based analytics and audit trails. Drawing on Nigerian case studies and international best practices, it assesses both the benefits (deterrence; improved security; traceability; reduced human error) and the challenges (cost, infrastructure, privacy, technical know-how). The chapter proposes sustainable strategies: institutional policies to mandate technology use; dedicated funding for secure systems; development of local technical capacity; ensuring ethical/data protection standards; and combining technology with strong human oversight. If properly implemented, these interventions can help restore fairness, trust, and excellence in the examination process across Nigeria’s higher education sector.